Identification of Factors and Components Affecting the Adult Literacy Curriculum with a Focus on Improving Social and Economic Skills in Tehran Province - Aliasgari, Majid; Sabaghian, Zahra; Niknam, Zahra; Qahari, Mohammad (Assessment and Practice in Educational Sciences, 2026)
This study aimed to design and validate a comprehensive model for the adult literacy curriculum with a specific focus on enhancing learners’ social and economic skills in Tehran Province. The research employed a qualitative approach using the grounded theory method. The statistical population consisted of experts in education, literacy instructors, and university specialists from Tehran Province. Through purposive snowball sampling, 20 experts with at least 29 years of experience and doctoral qualifications were selected for semi-structured interviews. Data were analyzed using open, axial, and selective coding to extract concepts, categories, and relationships among variables. The coding process led to the identification of causal, contextual, and intervening conditions, as well as strategies and outcomes. To ensure validity and reliability, data triangulation and expert validation were applied. The results revealed that the causal conditions of the adult literacy curriculum included infrastructures for work attachment, individuals’ internal orientation toward growth, and continuous skill development. The core category comprised intra-organizational characteristics, decision-making centered on the curriculum, conflict resolution around curriculum goals, institutional participation and support, organizational culture, structure, and staff skills. Contextual conditions were defined by adherence to values and behavioral principles, while intervening conditions encompassed environmental, legal, cultural, social, political, and economic factors. Strategic factors such as the formulation of a curriculum charter, implementation of essential managerial processes, and curriculum control led to positive outcomes including meritocracy, organizational justice, reduced corruption, improved leadership behavior, protection of labor rights, and stronger social relationships. Adult literacy education is most effective when it integrates moral, social, and economic dimensions through value-driven, participatory, and institutionally supported curriculum frameworks.